The impact of manufacturing flexibility on system performance: a simulation based approach - Gomez Valdez, Carlos Rafael (2010)
Manufacturing systems face now more than ever the effects of an uncertain environment, which is triggered by constantly changing customer needs. Numerous approaches have been proposed to provide manufacturing systems with the capability to satisfactorily perform under situations of uncertainty, particularly by improving their level of responsiveness. Manufacturing flexibility is a dimension of responsiveness which aims at reacting to unpredictable events with little penalty on performance.